Pengaruh Diskon dan Brand Ambassador Terhadap Niat beli Pada Konsumen Motor Yamaha (Studi Pada Dealer Yamaha Rolya Motor) - Alvirodihan, M Daffarel; Pandjaitan, Dorothy; Wulan, Mutiasari Nur (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The competition at the motorcycle producer level or at the dealer level is very high and intense. In the marketing process, purchase intention is an important element that reflects the psychological readiness of consumers in their decision-making. Yamaha is a major player in Indonesia but has recorded a significant decline compared to its competitors. Yamaha needs to optimize its marketing strategy to remain competitive in the market. This study aims to analyze the effect of discounts and brand ambassadors on the purchase intention of Yamaha motorcycle consumers, with a case study at the Yamaha Rolya Motor Dealer. The research method used is quantitative with a survey approach. Primary data was collected through questionnaires distributed to 200 prospective consumers. The Yamaha Rolya Motor Dealer in Bandar Lampung was selected using purposive sampling technique. Data were analyzed using multiple linear regression after passing validity and reliability tests. The results show that discounts (X1) do not have a significant effect on purchase intention (Y), while brand ambassadors (X2) have a positive and significant effect on purchase intention (Y). The presence of public figures such as comedian Komeng as Yamaha's brand ambassador effectively increases consumer interest and desire to purchase Yamaha motorcycles. This research contributes to the understanding of consumer behavior in the automotive industry context and can serve as a reference for future marketing strategies